The Urgency of Preserving Regional Languages through Local Educational Curriculum - Pamungkas, Susandi Decapriu Putra; Suputra, Gede Ngurah Darma; Fadillah, Dyah Ajeng Puspa; Rista, Mirsya Lila Agua; Arisandi, Sadira Ramadhani (Foremost Journal, 2023)
The use of local languages in the era of globalization is currently experiencing a decline. Based on field data, the utilization of local languages through local content education is minimally implemented by educational institutions. This poses a problematic situation as the use of local languages through local content education may vanish and erode due to the advancement of a more globalized world. In the Curriculum 13 itself, the use of local languages in educational institutions is mandated to be included as part of the local content subjects. However, in the "merdeka" (freedom) curriculum, the use of local languages is not obligatory, meaning it becomes conditional. This research adopts a qualitative research method, where the focus is on gathering information. Additionally, this study also employed a literature review approach, using journals, academic articles, and other. The research findings indicate that indeed, the use of local languages, content subjects has become rare in some cases, no longer applied, primarily due to the curriculum regulations. Therefore, the author suggests the issuance of a new policy that involves a collective reevaluation of the curriculum to ensure the enduring preservation of local languages in education. Keywords: Preservation local languages, local content, curriculum policy